The Development of Canva-Assisted Project Based Learning Model to Improve Students’ Critical Thinking Ability and Digital Literacy - Arif Maulana; Nelly Fitriani; Galih Dani Septiyan Rahayu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematics learning in elementary schools still tends to be dominated by conventional approaches, so it is not optimal in developing students' critical thinking skills and digital literacy, especially in the material of measurement data. This study aims to develop and test the effectiveness of the Project Based Learning (PjBL) model assisted by the Canva application in improving critical thinking skills and digital literacy of fifth-grade elementary school students. The study used a Research and Development (R&D) approach by adapting the simplified stages of Borg and Gall, including needs analysis, planning, product development, expert validation, revision, limited trials, and extensive trials. The subjects of the study were fifth-grade students in an elementary school in Purwakarta Regency. Data were collected through validation questionnaires, pretest-posttest tests, digital literacy observations, and interviews. The results showed that the Canva-assisted PjBL model was in the very feasible category based on expert assessments. The application of this model was proven to be able to significantly improve students' critical thinking skills with a medium N-gain value and improve students' digital literacy in all aspects with a very good category. Thus, the Canva-assisted PjBL model is effectively used as an alternative to innovative and contextual Mathematics learning in elementary schools.